2016
DOI: 10.1371/journal.pone.0157580
|View full text |Cite
|
Sign up to set email alerts
|

Different Effects of Eicosapentaenoic and Docosahexaenoic Acids on Atherogenic High-Fat Diet-Induced Non-Alcoholic Fatty Liver Disease in Mice

Abstract: Non-alcoholic fatty liver disease (NAFLD), the hepatic manifestation of metabolic syndrome, can progress to steatohepatitis (NASH) and advanced liver damage, such as that from liver cirrhosis and cancer. Recent studies have shown the benefits of consuming n-3 polyunsaturated fatty acids (PUFAs) for the treatment of NAFLD. In the present study, we investigated and compared the effects of the major n-3 PUFAs—eicosapentaenoic acid (EPA, C20:5) and docosahexaenoic acid (DHA, C22:6)—in preventing atherogenic high-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 56 publications
5
39
0
1
Order By: Relevance
“…However, in this study, there was no significant difference in the erythrocyte level of 22:6n3 between patients with and without NAFLD. Suzuki-Kemuriyama et al [35] reported that 22:6n3 intake was not effective for the reduction of hepatic triglyceride accumulation compared with 20:5n3, suggesting that 22:6n3 did not effectively reduce mRNA expression of fatty acid synthase.…”
Section: Discussionmentioning
confidence: 99%
“…However, in this study, there was no significant difference in the erythrocyte level of 22:6n3 between patients with and without NAFLD. Suzuki-Kemuriyama et al [35] reported that 22:6n3 intake was not effective for the reduction of hepatic triglyceride accumulation compared with 20:5n3, suggesting that 22:6n3 did not effectively reduce mRNA expression of fatty acid synthase.…”
Section: Discussionmentioning
confidence: 99%
“…Several animal models are widely used, such as high-fat diet or gene deletion mice, for studies of the mechanisms of fatty liver disease [16][17][18] . While macrofauna are considered ideal fatty liver models for US-based diagnosis research, in this study, a model of fatty liver using lactating thin-tail sheep was developed by restricted feeding.…”
Section: Discussionmentioning
confidence: 99%
“…The images of severe HS were usually accompanied by a thick sebum layer because obese sheep showed a high degree of fat mobilization in response to restricted feeding that resulted in severe HS, which usually induce attenuation of the echo affecting image evaluation. In addition, different from fatty liver disease caused by a high-fat diet, triglycerides first accumulate around the hepatic lobules, while liver triglycerides of NEB sheep were first detected around the liver portal area [17,24] . Hence, further studies are needed to determine whether the area of triglyceride accumulation impacts the vessel blurring score.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a low level of omega-3 FA increases CV risk, compromises cognition, and increases the risk for neurodegenerative diseases [65,66]. The association between PUFA levels and the progression of kidney disease has also been documented, with increased levels of omega-6 PUFA arachidonic acid (AA) being responsible for the upregulation of mediators of the renal fibrotic process [67][68][69]. In addition, a change in PUFA levels can increase the expression of angiopoietin like-4 (Angpt-4), which encodes a glycosylated, secreted protein containing a C-terminal fibrinogen domain that can act as an apoptosis survival factor for vascular endothelial cells, and could have a key role in nephritic syndrome [70].…”
Section: Proteinsmentioning
confidence: 99%